Case Report: Spontaneous Intramural Hematoma of the Colon Secondary to Low Molecular Weight Heparin Therapy - Zhu, Ye; Wang, Chao; Xu, Chao; Liu, Jia (Frontiers in Pharmacology, 2021)
Background Hematoma of the colon is considered as a rare hemorrhage complication for patients accepting low molecular weight heparin (LMWH) therapy. Only scarce cases of colon hematoma have been reported, usually in children or patients accepting warfarin therapy. Case summary A 76-year-old Chinese man was diagnosed with atrial fibrillation and heart failure, with cardiac function NYHA grade Ⅲ on March 21, 2018.This patient was given LMWH for anticoagulation therapy and developed a colon hematoma on the 3rddayof hospitalization. Abdominal computed tomography (CT) showed the thickening areas of the colon up to 110 mm×78 mm in thickness, which was a symptom of colon hematoma. The patient was ultimately treated by conservative treatment successfully. On March 27, the patient’s abdominal pain was alleviated and a CT scan showed that the intestinal hematoma was absorbed. Conclusion The most frequent minor bleeding events of LMWH anticoagulation are hemorrhage and subcutaneous hematoma. This case demonstrated that bowel hematoma despite its low incidence should be considered as an ADR of LMWH therapy, especially among patients who present with gastrointestinal symptoms.